GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 3966096 species occurrences available in GBIF matching the query: BasisOfRecord: Specimen PublishingCountry: Costa Rica. The dataset includes 3966096 records from 14 constituent datasets: 31917 records from Mollusca of Costa Rica (INBio). 10075 records from Nematoda of Costa Rica (INBio). 352692 records from Plantae of Costa Rica (INBio). 3276498 records from Insecta of Costa Rica (INBio). 43 records from Digital Florula - Las Cruces Biological Station. 281 records from Myriapoda of Costa Rica (INBio). 56 records from Onychophora of Costa Rica (INBio). 191859 records from herbario. 1764 records from Arachnida of Costa Rica (INBio). 769 records from Digital Florula - Palo Verde Biological Station. 630 records from Wilson Botanical Garden - Las Cruces Biological Station. 3129 records from Herbarium - Las Cruces Biological Station. 46288 records from Colección nacional de zoología. 50095 records from Fungi of Costa Rica (INBio). Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences